(3GdHQgGf GdcGTa aj EYLGR GdbQBf GdcQjes - (3ceGd GdOjf CHh GdecGQe YHO GdhGMO Hf YHO GdcQje Hf Nda GdRedcGfis; (3eMeO Hf RjO Hf Ydj Hf GdMSjf GdhGSWj, CHh YHO Gddg,J (B307 (3g` s
(3ChdgG (B:s
(3Hc Gddge GdhGMO GdCRdi GdHGbi GdSQeOi GdaUd GdChd ai MbjbI Yde GdHjGf hGdZQV efg hWQjb JMUjdg s
(3BNQgG (B:s
(3hddg GdbGFd ef Ufa abO GSJgOa aEf CUGH abO GSJYWa hEf CSGA abO GJbPa hGddg GdeCehd ai JVYja GdKhGH Je s
(3GdfSNI efbhdI Yf CUd cJH Ydjg Cf GdeDda aQZ ef JCdja GdcJGH (B645s
(3HgG fXGe GdJYbjHIs
(3fSNI KGdKIZes
(3hQO GdYfhGf ai cTa GdXfhf GdJHjGf ai Yde GdHjGf hdjS dg Ci CUd ai GdeNWhWIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdJaSjQ hYdhe GdbQBfs